Effects of a structured exercise therapy on health-related quality of lifein pediatric stem cell transplantation - Jung, Michael Wilhelm; Schubert, Patric; Stephenson, Antonia; Bader, Peter (Wydawnictwo Akademii Wychowania Fizycznego im. Polskich Olimpijczyków we Wrocławiu, 2024)
Introduction. This randomized controlled trial investigated the effects of exercise therapy on cancer-related fatigue (CRF) andits association with health-related quality of life. The effect of exercise therapy on the quality of life of children after stem celltransplantation has not been extensively studied to date.Methods. Seventy-two children and adolescents after stem cell transplantation were randomly assigned to either an exercisetherapy intervention group (IG) or a control group (CG). The children in IG received sports therapy, while the children in the CGengaged in concentration tasks, memory games, and quizzes.Results. Significant improvements in CRF were found in IG only after discharge from the hospital. The improved CRF correlated significantly with increased health-related quality of life. However, during the inpatient phase, there was a rapid increasein CRF initially, which was accompanied by a significant reduction in health-related quality of life.Conclusions. Exercise therapy can help reduce CRF and, therefore, increase health-related quality of life after the inpatientphase.
Keywords: pediatric oncology; childhood cancer; stem cell transplantation; physical therapy; quality of life; fatigue